Temperatura na emergência de quatro variedades de mamoeiro - De Andrade, Renata Aparecida [UNESP]; Jasper, Samir Paulo [UNESP] (My University, 2013)
This research was realized to check the response of four varieties of papaya for emergence at different temperatures. The experiment was conducted at UNESP, Campus of Jaboticabal city, São Paulo state, Brazil, using seeds of four varieties of papaya, two of the group Solo (Sunrise Solo 722 and Golden) and two of the group Formosa (Rubi Incaper 511 and Calimosa), submitted to four temperatures: constant at 20°C, 25°C, 30°C and alternating 20/30°C (8 hours at 30°C and the remainder at 20°C), with a photoperiod of 8 hours of light/day. The study was conducted in factorial 4 x 4 (four varieties of papaya and four temperatures), using a completely randomized design with four replicates per treatment and 20 seeds in each. The percentage of emergence was evaluated weekly and the data were subjected to analysis of variance and comparison of means by Tukey test at 5% probability. The results showed that the highest percentage of emergency occurs in alternating temperatures (20/30°C) and the varieties of the group Solo also emerge satisfactorily at temperatures of 25°C and 30°C constant.
Temperature seedling emergence of four papaya cultivars
Keywords: Carica papaya L.; Plant propagation; Seed